Aesthetics, Ideology, and Ethics of Remembrance in Red Detachment of Women (Hongse Niangzi Jun, 红色娘子军). Issue 1 (2nd January 2017) - Mullis, Eric
ABSTRACT: The Red Detachment of Women is a ballet that was developed under the supervision of the Chinese Communist Party in the period leading up to the Cultural Revolution. It features a distinctive approach to ideological content that draws on martial arts, folk dance, and Beijing Opera traditions, and continues to appeal to contemporary audiences in China. I consider the aesthetics of the weapon advanced by the ballet and the ethical and political implications of the National Ballet of China's continued performances of a ballet that celebrates a time of persecution of ordinary Chinese citizens.